MPS 05-03 RELATIONSHIP BETWEEN INCIDENCE OF OBSTRUCTIVE SLEEP APNOE SYNDROME AND ATRIAL FIBRILLATION AND THE SERUM URIC ACID IN ESSENTIAL HYPERTENSION PATIENTS. (September 2016) - Diaconu, Nadejda; Grosu, Aurel; Caldare, Liliana; Cuzor, Tatiana; Gratii, Cristina
Abstract : Objective: Our aim was to investigate the relationship of SUA with HTN, AF as also the correlation of SUA with sleep apnea and specific diastolic echocardiographic parameters in hypertensive patients. Design and Method: We prospectively enrolled 418 hypertensive patients and 103 controls. The group of hypertensives was divided into: subgroup A (N = 78): with AF and subgroup B (N = 443): in sinus rhythm. We investigated the differences of SUA levels among the groups. In the second part we studied the correlation of SUA with apnea hypopnoea index (AHI), left atrial diameter (LA), left ventricular mass (LVM) and pulse wave velocity. Results: The mean age of patients with AF was (67.5 ± 10.2) yr vs. (61.8 ± 10.1)yr in subgroup B. Comparative analysis showed that SUA levels were significantly increased in patients with hypertension and AF (9.7 ± 6.1 mg/dl vs group B: 6.0 ± 1.4 mg/dl vs control group: 5.4 ± 1, 2 mg/dl, p < 0.01). After adjustment for LAD, LVEDD, LVMI, LVEF, TC, SUA and age logistic regression analysis showed that only age (OR: 1.054; 95% CI: 1.019–1.090, p = 0.002), LAD (OR: 1.173; 95% CI: 1.114–1.235; p < 0.001) and LVEF (OR: 0.942; 95% CI: 0.914–0.971; p < 0.001) were independently associated with AF, while SUA was not independently associated with AF in EH patients. Patients in subgroup A presented more often sever OSAS (58% vs 26%, p < 0, 05). Adjusted for age, BMI, BP, the patients with hyperuricemia presented greater AHI, mean SpO2, frequency of SpO2 decreased >=4% and >=5%. The UA levels significantly increased with the severity of OSAS. Conclusions: Increased SUA levels are not independently associated with AF in patients with hypertension, while age, LAD and LVEF are independently associated with AF in patients with EH. A strong association was found between UA levels and OSAS in a large number of hypertensive patients with AF.